2003
DOI: 10.1097/00001756-200306110-00002
|View full text |Cite
|
Sign up to set email alerts
|

Attention and emotion: an ERP analysis of facilitated emotional stimulus processing

Abstract: Recent event-related potential studies observed an early posterior negativity (EPN) reflecting facilitated processing of emotional images. The present study explored if the facilitated processing of emotional pictures is sustained while subjects perform an explicit non-emotional attention task. EEG was recorded from 129 channels while subjects viewed a rapid continuous stream of images containing emotional pictures as well as task-related checkerboard images. As expected, explicit selective attention to target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
317
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(381 citation statements)
references
References 26 publications
57
317
1
6
Order By: Relevance
“…We found the EPN to be consistently enhanced to emotionally valent (positive and negative) as compared to neutral words, replicating previous results of native language research (Herbert et al, 2008;Kissler et al, 2009;Scott et al, 2009). Importantly, this valence effect showed a bilateral occipito-temporal negativity, which is the typical scalp distribution of the EPN (e.g., Schupp et al, 2003). However, the EPN emotion effect in the present study was observed slightly later than emotion effects recently reported by others (Herbert et al, 2008;Kissler et al, 2007).…”
Section: Discussioncontrasting
confidence: 50%
“…We found the EPN to be consistently enhanced to emotionally valent (positive and negative) as compared to neutral words, replicating previous results of native language research (Herbert et al, 2008;Kissler et al, 2009;Scott et al, 2009). Importantly, this valence effect showed a bilateral occipito-temporal negativity, which is the typical scalp distribution of the EPN (e.g., Schupp et al, 2003). However, the EPN emotion effect in the present study was observed slightly later than emotion effects recently reported by others (Herbert et al, 2008;Kissler et al, 2007).…”
Section: Discussioncontrasting
confidence: 50%
“…Typically, this takes the form of larger amplitudes to emotionally-valenced stimuli (Dolcos & Cabeza, 2002;Eimer, Holmes, & McGlone, 2003). When utilizing faces, fearful faces have elicited larger P300s than neutral faces (Eimer & Holmes, 2002;Holmes et al, 2003) but angry faces have also elicited larger P300s than both happy and neutral facial expressions (Schupp, et al, 2003(Schupp, et al, , 2004 which may reflect the greater arousal associated with viewing angry compared with happy expressions. Past P300 research showing larger responses to more arousing stimuli predicts larger P300s to angry expressions.…”
Section: Erp Componentsmentioning
confidence: 99%
“…Negative-going waveforms are also greater within 300 ms following presentation of negative versus positive faces and liked versus disliked faces (Pizzagalli et al, 1999;Pollak and Tolley-Schell, 2003;Schupp et al, 2003). In particular, a posterior face-specific component, N170, is modulated by emotion (Batty and Taylor, 2003;Eger et al, 2003;Pizzagalli et al, 1999), and is greater in the right hemisphere (Bentin et al, 1996).…”
mentioning
confidence: 94%